2006
DOI: 10.1191/0960327106ht621oa
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium glutamate-induced oxidative damage and genotoxicity in the rat: modulatory role of vitamin C, vitamin E and quercetin

Abstract: Monosodium glutamate (MSG) continues to function as a flavor enhancer in West African and Asian diets. The present study examines the modulatory effects of dietary antioxidant vitamin C (VIT C), vitamin E (VIT E) and quercetin on MSG-induced oxidative damage in the liver, kidney and brain of rats. In addition, the effect of these antioxidants on the possible genotoxicity of MSG was investigated in a rat bone marrow micronuclei model. MSG administered intraperitoneally at a dose of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
135
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(178 citation statements)
references
References 33 publications
27
135
1
6
Order By: Relevance
“…Farombi and Onyema (2006), who found that the monosodium glutamate when was administered intraperitoneally at 4 mg/g of body weight dose, increased the formation of malondialdehyde (MDA) in the rat's liver and brain. Farombi and Onyema (2006) showed significant reduction of the TBA levels of the rats treated with monosodium glutamate, with simultaneous administration of vitamin C, vitamin E and queracetin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Farombi and Onyema (2006), who found that the monosodium glutamate when was administered intraperitoneally at 4 mg/g of body weight dose, increased the formation of malondialdehyde (MDA) in the rat's liver and brain. Farombi and Onyema (2006) showed significant reduction of the TBA levels of the rats treated with monosodium glutamate, with simultaneous administration of vitamin C, vitamin E and queracetin.…”
Section: Resultsmentioning
confidence: 99%
“…Farombi and Onyema (2006), who found that the monosodium glutamate when was administered intraperitoneally at 4 mg/g of body weight dose, increased the formation of malondialdehyde (MDA) in the rat's liver and brain. Farombi and Onyema (2006) showed significant reduction of the TBA levels of the rats treated with monosodium glutamate, with simultaneous administration of vitamin C, vitamin E and queracetin. Rimbau et al (1999) reported the antioxidant potential of the protein Cphycocyanin extracted from S. platensis and showed that the metabolites of this protein had the ability to cross the blood-brain barrier, thereby conferring a protective effect of oxidative stress on the hippocampus of the rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of AA on MSG-induced oxidative stress It has been suggested that MSG can induce oxidative stress in the rat brain and that antioxidants may be effective at ameliorating this effect [35] . Therefore, we investigated the levels of lipid peroxidation and the activity of an antioxidant enzyme in the hippocampus and cortex.…”
Section: Effects Of Aa On Msg-induced Cognitive Deficitsmentioning
confidence: 99%
“…Further negative impact of MSG may occur if an adult consumes MSG with a dose more than 3g/day while one table spoon averagely comprises 4-6 g (Walker, 2000). MSG also triggers hypertension, asthma, cancer, diabetes, paralysis and decreasing intelligence.The given MSG by 4 mg/gBW toward mice resulted in the increasing amount of malondyaldehide (MDA) in lever, kidney, and brain (Farombi and Onyema, 2006 organ is interrupted. Hypothalamus secretes gonadotrophin releasing hormone that stimulates secretion of Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH) from anterior hypophysis.…”
Section: Introductionmentioning
confidence: 99%